2018
DOI: 10.1039/c8fo00888d
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic and genetic response to probiotics supplementation in patients with diabetic nephropathy: a randomized, double-blind, placebo-controlled trial

Abstract: This study was carried out to evaluate the effects of probiotics administration on the metabolic and genetic profiles in patients with diabetic nephropathy (DN). This was a randomized, placebo-controlled clinical trial with homeostasis model of assessment-estimated insulin resistance (HOMA-IR) as the primary and other metabolic profiles, and biomarkers of inflammation and oxidative stress as the secondary outcomes. This randomized, double-blind, placebo-controlled clinical trial was performed on 60 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 44 publications
1
83
0
2
Order By: Relevance
“…43 Another study showed that probiotic supplementation had beneficial effects on glycemic control and markers of cardiometabolic risk. 44 A meta-analysis showed that probiotic supplementation decreased serum insulin and insulin resistance, but it had no beneficial effect regarding kidney function, body weight and lipid profiles, with a moderate positive effect regarding some oxidative stress biomarkers. 45 Another meta-analysis showed the benefits of probiotic supplementation on the reduction of inflammation, oxidative stress and on the amelioration of renal function biomarkers in subjects with diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Another study showed that probiotic supplementation had beneficial effects on glycemic control and markers of cardiometabolic risk. 44 A meta-analysis showed that probiotic supplementation decreased serum insulin and insulin resistance, but it had no beneficial effect regarding kidney function, body weight and lipid profiles, with a moderate positive effect regarding some oxidative stress biomarkers. 45 Another meta-analysis showed the benefits of probiotic supplementation on the reduction of inflammation, oxidative stress and on the amelioration of renal function biomarkers in subjects with diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that probiotic honey consumption for 12 weeks among DN patients had beneficial effects on insulin metabolism, total‐/HDL‐cholesterol, serum hs‐CRP, and plasma MDA levels, but did not affect other metabolic profiles 43 . Another study showed that probiotic supplementation had beneficial effects on glycemic control and markers of cardiometabolic risk 44 . A meta‐analysis showed that probiotic supplementation decreased serum insulin and insulin resistance, but it had no beneficial effect regarding kidney function, body weight and lipid profiles, with a moderate positive effect regarding some oxidative stress biomarkers 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The increase in insulin sensitivity and plasma total glutathione, and decrease in FBG, HOMA-IR values, and malondialdehyde, high-sensitive C-reactive protein were observed in the probiotic-treated group. The results suggested that probiotic consumption improved the cardiovascular diseases risk factors in DN patients [37].…”
Section: Diabetes Patientsmentioning
confidence: 91%
“…Based on the randomized, placebo-controlled, double-blind studies [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] reviewed in the present article, the hypocholesterolemic effect of the probiotics was not significantly influenced by the diet. Studies reported based on the intervention of single-strain probiotic (E. faecium M-74 along with selenium [27]; Saccharomyces cerevisiae var.…”
Section: Opinion On the Hypocholesterolemic Effect Of Reviewed Probiomentioning
confidence: 99%
See 1 more Smart Citation